Endoscope-assisted resection of brainstem cavernous malformations - Oertel, Joachim; Fischer, Gerrit; Linsler, Stefan; Huelser, Matthias; Sippl, Christoph; Teping, Fritz (Neurosurgical Review, 2022)
Targeted surgical precision and minimally invasive techniques are of utmost importance for resectioning cavernous malformations involving the brainstem region. Minimisation of the surgical corridor is desirable but should not compromise the extent of resection. This study provides detailed information on the role of endoscopy in this challenging surgical task. A retrospective analysis of medical documentation, radiologic studies and detailed intraoperative video documentation was performed for all consecutive patients who underwent surgical resection of brainstem cavernous malformations between 2010 and 2020 at the authors’ institution. A case-based volumetry of the corticotomy was performed and compared to cavernoma dimensions. A total of 20 procedures have been performed in 19 patients. Neuroendoscopy was implemented in all cases. The mean size of the lesion was 5.4 (± 5) mm3. The average size of the brainstem corticotomy was 4.5 × 3.7 (± 1.0 × 1.1) mm, with a median relation to the cavernoma’s dimension of 9.99% (1.2–31.39%). Endoscopic 360° inspection of the resection cavity was feasible in all cases. There were no endoscopy-related complications. Mean follow-up was 27.8 (12–89) months. Gross-total resection was achieved in all but one case (95%). Sixteen procedures (80%) resulted in an improved or stable medical condition. Eleven patients (61.1%) showed further improvement 12 months after the initial surgery. With the experience provided, endoscopic techniques can be safely implemented in surgery for BSCM. A combination of neuroendoscopic visualisation and neuronavigation might enable a targeted size of brainstem corticotomy. Endoscopy can currently be considered a valuable additive tool to facilitate the preparation and resection of BSCM.
CRIS-Team Scopus Importer:2023-12-20
Keywords: Brainstem; Cavernoma; Cavernous malformation; Endoscopic neurosurgery; Neuroendoscopy